Use of topical Purified Solasodine of Solanum Melongena Peel Origin in the Treatment of Moderate to Severe Palmar Arsenic Keratosis (Sir Salimullah Medical College Journal, 2025)
Background: Bangladesh has one of the highest rates of arsenic poisoning in the world. Arsenicosis often manifests as arsenic keratosis on the sole and palm of the hand. Brinjal (solanum melongena) is a common vegetable in Bangladesh and elsewhere. A study demonstrated that an ointment comprising a crude extract of Solanum melongena peel is effective in treating arsenic keratosis. This study was conducted to use the particular component present in brinjal peel which can cure arsenic keratosis. Methods: The Bangladesh Medical University department of pharmacology reported that S. melongena peel crude extract topical ointment was helpful in arsenical keratosis in two tests. The present study observed arsenic keratosis lesions or nodular size following 12 weeks of pure solasodine ointment therapy. A total of 20 patients were enrolled based on the established inclusion and exclusion criteria. Of the patients, 14 exhibited severe keratosis, while 6 presented moderate keratosis. One patient with arsenic keratosis discontinued participation during the follow-up period due to complaints of heaviness at the application site. Nineteen patients completed a 12-week therapy regimen. Results: This prospective observational clinical trial reports that patients with palmar arsenical keratosis exhibited a mean (± SD) keratotic skin lesion size of 31.7±12.4 mm² prior to the intervention and 7.2±6.8 mm² following the intervention. The reduction percentage was 77.6 ± 19.8, with a p-value of 0.0001. Statistical analysis indicated significance. Conclusion: The research that proved solasodine, a compound found in S. melongena peel, was what heals arsenical keratosis lesions.Sir Salimullah Med Coll J 2024; 32: 76-83